Valorization of Oil Palm Empty Fruit Bunch Waste Enhanced with Molasses for Erythritol Production - Setiabang, Jeffersen Hosea; Fildy, Michael Ryan; Limawan, Kezia Zefanya; Widiyono, Advent Roan; Yonas, Nathanael Darrell; Nataniel, Jocelyn; Saputra, Indra Kurniawan; Kembaren, Riahna (Biosaintifika: Journal of Biology & Biology Education, 2025)
Indonesia, a leading palm oil producer, generates 1,250 tons of Oil Palm Empty Fruit Bunches (OPEFB) waste daily, typically disposed of through polluting combustion. This study explores repurposing OPEFB as a substrate for erythritol production, a popular sweetener with minimal impact on blood sugar. The research utilized Moniliella pollinis mutant SP5, a yeast capable of producing erythritol from various substrates. The process involved acid hydrolysis of OPEFB followed by fermentation. When fortified with 15% v/v molasses, OPEFB successfully served as an optimal carbon source for erythritol production, achieving a mass yield of 0.2878 g/g. Further improvement came through the use of ethyl methane sulfonate (EMS) mutagenesis, with the best mutant (mutant 7) reaching a yield mass of 0.3298 g/g and volumetric productivity of 0.0534 g/L/h. This research aims to advance Indonesia's self-sufficiency in erythritol production while providing a sustainable solution for OPEFB waste reduction, simultaneously addressing economic and environmental concerns.